Bridging skills gaps in maritime engineering: Aligning education with industry and sustainability demands - Larsen Barasa; Bambang Kurniadi; Imam Fahcruddin (Universitas Muhammadiyah Malang, 2025)
The maritime industry is undergoing rapid transformation, driven by technological advancements and global sustainability imperatives. However, a persistent skills gap exists between the competencies provided by maritime education programs and the evolving demands of the industry—particularly in relation to green technologies and advanced engineering practices. This study offers a timely contribution by examining the perspectives of maritime professionals, educators, and graduates to identify critical skill gaps and propose actionable strategies for educational reform. Employing a qualitative approach, the research involved semi-structured interviews with 13 industry professionals, 14 educators, and 23 recent graduates. Thematic analysis revealed notable deficiencies in applied technical skills, problem-solving abilities, and sustainability knowledge, despite strong theoretical foundations. The findings highlight the urgent need for curriculum modernization, stronger collaboration between academia and industry, and greater investment in practical training resources. Addressing these gaps is essential to developing a skilled, adaptable, and sustainability-oriented maritime workforce capable of supporting innovation and maintaining global competitiveness. This study contributes to the ongoing discourse on maritime education reform by offering practical recommendations for aligning vocational training with the current and future needs of the maritime sector.